How Much Do Workers Actually Value Working from Home? - Markus Nagler; Johannes Rincke; Erwin Winkler (Center for Economic Studies and ifo Institute (CESifo), 2022)
Working from home (WFH) has become ubiquitous around the world. We ask how much workers actually value this job attribute. Using a stated-preference experiment, we show that German employees are willing to give up 7.7% of their earnings for WFH, but they value other job attributes more. For instance, the willingness-to-pay is 13.2% for reducing a commute of 45 to 15 minutes. WFH valuations are heterogeneous across workers and WFH substantially contributes to compensation inequality across education levels. Finally, valuations meaningfully interact with commuting distance and WFH reduces (but does not close) the gender gap in willingness-to-pay to avoid commuting.
Keywords: J20; J31; J33; J81; 330; working from home; working conditions; inequality; commuting; compensating wage differentials